Reducing polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/F) emissions from a real-scale iron ore sinter plant by adjusting its sinter raw mix. (20th January 2016) - Chen, Yu-Cheng; Kuo, Yu-Chieh; Chen, Mei-Ru; Wang, Ying-Fang; Chen, Ching-Hwa; Lin, Ming-Yeng; Yoon, Chungsik; Tsai, Perng-Jy
Abstract: This study was conducted in a real-scale iron ore sinter plant for reducing emissions of polychlorinated dibenzo- p -dioxins and dibenzofurans (PCDD/Fs) from the iron ore sintering process via the adjustment of its sinter raw mix. Based on operating condition of the selected plant, four experimental campaigns of Cref (currently used raw mix, served as the reference), CH (modified from Cref, with a 15% increase in hematite but 15% decrease in limonite), CH, EP (modified from CH, without electrostatic precipitator (EP) and blast furnace (BF) flue dusts), and CH, EP, W (modified from CH, EP, with a 0.5 wt% increase in water content) were chosen. For each experimental campaign, three replicate samples of PCDD/Fs were collected from the flue gases, and the sinter productivity and sinter strength were measured simultaneously. In comparison with Cref, the most significant reductions in PCDD/F and I-TEQ emissions was found in CH, EP (=68% and 76%, respectively), and the main reduction was found in PCDFs (54–76% decrease). CH could reduce emissions of PCDD/Fs and I-TEQ by 47% and 51%, respectively. But the addition of water contents (i.e., CH, EP, W ) did not result in further reductions. Since sinter productivity and sinter strength of all experimental campaigns were quite similar, CH, EP could be a promising raw mix for reducing PCDD/F emissions from the sintering process. Highlights: Reducing PCDD/F emissions from a real-scale iron ore sinter plant through the adjustment of its sinter raw mix. Four experimental campaigns were chosen based on operating condition of the selected plant. Replicate samples of PCDD/Fs were collected from the flue gases. Sinter productivity and sinter strength were measured simultaneously. A raw mix was recommended for reducing PCDD/F emissions.